Analisis Pelaksanaan Program Puskesmas Dalam Menurunkan Prevalensi Stunting Di Desa Dolok Saribu Kecamatan Pagaran - Purba, Yenni Tulus; Yusnadi, Yusnadi (JUKEJ : Jurnal Kesehatan Jompa, 2025)
This research aims to analyze the implementation of the community health center program in reducing stunting in Dolok Saribu village. The study used a descriptive qualitative phenomenological approach. Informant selection was conducted using purposive sampling. Data collection involved interviews, observations, and documentation, followed by data reduction, data presentation, and drawing conclusions from the collected data. The results showed that the implementation of the community health center program to reduce the prevalence of stunting has been carried out in every work area of the community health center, including Dolok Saribu village, with a monthly schedule that includes immunization programs, nutritional counseling, and measuring height and weight by age. All programs are conducted by community health center staff in accordance with their area of expertise. However, the implementation of the community health center program has not yet reached optimal results due to the community's lack of active participation in the program.